Hollow PtCu nanorings with high performance for the methanol oxidation reaction and their enhanced durability by using trace Ir. Issue 7 (3rd February 2020) - Shi, Yan; Fang, Yan; Zhang, Genlei; Wang, Xianshun; Cui, Peng; Wang, Qi; Wang, Yuxin
Abstract : Cu atoms and a hollow structure are helpful for the improvement of the MOR activity of Pt. Trace Ir atoms might promise a superior durability for the Pt-based catalysts while maintaining the MOR catalytic activity. Abstract : Platinum–copper (PtCu) alloy nanostructures represent an emerging class of electrocatalysts for the methanol oxidation reaction (MOR) in direct methanol fuel cells (DMFCs), but practical applications have been limited by catalytic activity and durability. In this study, we developed an efficient one-pot hydrothermal strategy to prepare unique PtCu alloy nanorings (NRs) with a highly open hollow structure. The formation process of the hollow NR structure includes the initial formation of pure solid Cu nanocrystals (NCs), the subsequent galvanic replacement reaction between Cu and Pt 2+, and the co-deposition of Pt and Cu atoms at the edges. The r-Pt0.75 Cu/C catalyst, that is, Pt0.75 Cu NRs with an input Pt/Cu molar ratio of 0.75/1 supported on carbon black exhibited superior MOR performance, with a mass activity of 2.175 A mgPt −1 and a specific activity of 52.26 A m −2, which are 4.5- and 6.6-fold enhancements relative to those of commercial PtRu/C-JM, respectively. Impressively, the durability of Pt0.75 Cu NRs for the MOR can be enhanced dramatically by doping with trace Ir. The mass activity loss of r-Pt0.75 Ir0.05 Cu/C, that is, Ir-doped Pt0.75 Cu NRs supported on carbon black, was only 7.44%, much smaller than those of r-Pt0.75 Cu/C (37.76%) and PtRu/C-JM (50.27%) after 10 000 CV cycles. This work provides a strategic design of efficient PtCu catalysts for the MOR.